Building Brand Trust through Content: How Social Media Marketing Influences Muslim Consumers' Purchasing Decisions - Alamayreh, Esraa M.; Fadhil, Khalid; Issam, Nash'at (Journal of Posthumanism, 2025)
This study examines the impact of social media marketing strategies on the purchase decisions of Muslim consumers in Jordan, focusing on the mediating role of brand trust. The study adopted a quantitative approach with a sample of 312 Muslim consumers in Jordan, and Smart PLS-SEM was used to analyze the data. The study investigated four main hypotheses. The results revealed that social media marketing strategies positively influence both consumer brand trust and purchase intention among Muslim consumers. Furthermore, consumer brand trust has a significant positive impact on purchase decisions. However, the study confirms the mediating role of consumer brand trust in the relationship between social media marketing strategies and purchase decisions. These findings emphasize the importance of building brand trust through effective social media marketing strategies to positively influence Muslim consumers’ purchase decisions. They also suggest that companies should focus on developing meaningful and engaging content that is consistent with the values and culture of Muslim consumers and be interactive and transparent in communicating with their audience on social media platforms. It is also recommended to use different types of content, such as images, videos, and stories, to enhance engagement and attract consumers’ attention.